Konseling Kiai terhadap Manajemen Pesantren - Ainur Rofiq; Sutopo (Conseils : Jurnal Bimbingan dan Konseling Islam, 2022)
Pesantren is not only based on one curriculum but must use a broad curriculum. This is left to the elastic adjustment between the will of the kiai and the abilities of the students individually. Because every pesantren has a different curriculum, the series of trio components of Islamic teachings in the form of faith, Islam and ihsan or doctrines, rituals, and mysticism have become a concern as the curriculum taught to their students. The transition of prayer room (surau) or mosque being developed into a boarding school turns out to bring changes in teaching materials from mere knowledge to a science. In further developments, students need to be given not only knowledge related to practical-pragmatic daily rituals, but also sciences that smell like reasoning that uses revelation references such as Kalam science, eventhough the usefull sciences for the right approach to God like Sufism. The science of kalam or the science of monotheism provides understanding and belief in the oneness of Allah, fiqh provides ways of worship as a logical consequence of the faith one has in perfecting worship in order to become a person who is truly close to Allah. With the aim that this pesantren can develop in accordance with the times, the used model is the model and paradigm of pesantren education which is the orientation and foundation in the curriculum of pesantren educational institutions, which includes: basic, goals, concepts and values, with this model hope boarding school can be achieved.